Organochlorine Exposure Influences the Cellular Morphology of Red Algae Eucheuma denticulatum (N.L. Burman) Collins & Hervey, 1917 - Tumembouw, Sipriana S; Rompas, Rizald M; Lumenta, Cyska; Paulus, James J H; Lasut, Markus T; Mantiri, Desy M H (Jurnal Ilmiah Perikanan dan Kelautan, 2025)
Graphical Abstract   Highlight Research 1. The research demonstrates organochlorine influences the nanoparticle and the thickness of red algae cellulose. 2. SEM analysis with EDS visualization showed an accumulation of Chlorine (Cl) in the thallus of red alga. 3. This research is essential to prevent and reduce the disposal of organochlorines into the environment because they can accumulate in soil, water, and air. 4. The disposal of organochlorines can also remain for years in the environment, which in turn will accumulate in food chains and negatively affect ecosystems and marine animals.     Abstract Organochlorine compounds not only pollute marine waters but also interfere with the survival of marine biota. Organochlorine compounds absorbed by organisms disrupt metabolism and inhibit cellular functions. The implication of this research is to prevent and reduce the disposal of organochlorines into the environment because they can accumulate in soil, water, and air, remaining for years in the environment. This accumulation can affect food chains and negatively affect ecosystems and marine animals.This research aimed to investigate the impact of organochlorine content on the surface morphology and biomineral characteristics of the red alga E. denticulatum cells. Electron Microscope (SEM) analysis was used to observe particle morphology surfaces down to 1 nm, while Energy Dispersive Spectroscopy (EDS) was used to analyze the specimens' element composition and chemical characteristics. Energy Dispersive Spectroscopy (EDS) analysis revealed that red algae had the highest content of Chlorine (Cl) at 57.20%, followed by Sodium (Na) at 34.84%, Oxygen (O) at 5.21%, Calcium (Ca) at 1.64%, and the lowest element being Sulfur (S) at 1.11%. Overall, this research demonstrates the negative impact of organochlorine content on the morphological structure and biomineral composition of E. denticulatum, highlighting the need for effective measures to prevent and reduce organochlorine pollution in marine environments. Further research could focus on specific mechanisms of organochlorine toxicity and potential remediation strategies.